(untitled) (Conferencea, 2023)
Fatigue and apathy after a long working day is a natural and normal phenomenon. To get back to normal, a healthy person just needs to get enough sleep or make it to the end of the week off. But if rest does not help to return to a healthy state and fatigue does not leave a person, it is worth thinking about visiting a doctor.